Граничний вплив неідентичності ємнісних елементів високовольтного плеча на частотні характеристики подільника напруги (аналітичне дослідження) - Бржезицький, Володимир Олександрович; Гаран, Ярослав Олександрович; Держук, Андрій Олександрович; Проценко, Олександр Ростиславович; Троценко, Євгеній Олександрович; Dixit, Mandar Madhukar (Національний технічний університет "Харківський політехнічний інститут", 2021)
На основі раніше розвинутої теорії широкосмугових подільників напруги з паралельно-послідовним з’єднанням R-, C- елементів вперше одержані аналітичні вирази для амплітудно-частотної та фазо-частотної характеристик подільника напруги з урахуванням граничного випадку неідентичності ємнісних елементів високовольтного плеча. Визначений загальний характер залежностей частотних характеристик від значення допуску ємнісних елементів, коефіцієнта ділення подільника напруги в широкому діапазоні зміни частоти. Запропоновані спрощені апроксимуючі вирази для максимальних значень частотних характеристик та визначена їх похибка. Рекомендовано уведення в нормативну документацію широкосмугових подільників напруги відкоригованого значення коефіцієнта ділення.

Determination in the analytical form of the maximum limiting influence of the non-identity of the capacitive elements of the high-voltage arm on the amplitude-frequency characteristic and phase-frequency characteristic of the voltage divider with parallel series connection of R-, C- elements of the high-voltage arm. Methodology. Based on the previously developed theory of broadband voltage dividers with parallel-series connection of R-, C-elements, analytical expressions for amplitude-frequency and phase-frequency characteristics of the voltage divider are obtained and investigated taking into account the limit case of non-identical capacitive elements of high-voltage arm. Results. The nature of the dependencies of the frequency characteristics of the broadband voltage divider on the value of the tolerance of the capacitive elements of the high-voltage arm, the division factor of the voltage divider in a wide range of frequency changes is determined. Simplified approximating expressions for the maximum values of frequency characteristics of the voltage divider are proposed and their error is determined. Originality. For the first time in the analytical form the limiting influence of non-identity of capacitive elements of a high-voltage arm of a voltage divider on its frequency characteristics is considered. A mathematical model of this influence is constructed and the limit values of frequency characteristics of the voltage divider are determined. Practical value. It is recommended to introduce into the normative documentation of broadband voltage dividers the corrected value of the division factor, which allows to significantly reduce the deviation of the actual value of the division factor of the voltage divider from the normalized value in a wide range of frequency changes.
Ultimate effect of non-identity of capacitive elements of high-voltage arm on frequency characteristics of voltage divider (analytical research)
Keywords: аналітичні вирази; допуск ємнісних елементів; коригування параметрів; analytical expressions; tolerance of capacitive elements; parameters adjustment